The Effectiveness Of The Exchange Rate on The Amount of Foreign Exchange Reserves in Indonesia - Dwitama, Dimas Rastra; Nasution, Lia Nazliana; Efendi, Bakhtiar; Sari, Wahyu Indah (Economic: Journal Economic and Business, 2022)
This study aims to analyze the interaction variables of fiscal transfer policy variables. (Foreign Exchange Reserves, Imports, Exports, Exchange Rates and GDP). This study uses secondary data or from 2000 - 2019. The data analysis model in this study uses the Vector Autoregression (VAR) model and is sharpened by Impulse Response Function (IRF) Analysis, Forecast Error Variance Decomposition (FEVD). The results of the VAR analysis show that previously (t – p) contributed to the current variable, both alone and to other variables. The results of the FEVD analysis show that all variables have a major contribution to the variables themselves in the short, medium and long term, namely Foreign Exchange Reserves, Imports, Exports, Exchange Rates and GDP. The results of the analysis of each variable of monetary policy transmission and the effectiveness of the Exchange Rate on Reserves Short, medium and longterm exchange rates show that policy transmission can maintain the Indonesian economy